Perception of Students of the Da'wah Management Study Program of UIN Raden Fatah Palembang on the Values of Da'wah in the Film Bid'ah - Emelda; Hidayat HT; Hartika Utami Fitri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This thesis is entitled "Perception of students of the Da'wah Management Study Program of UIN Raden Fatah Palembang towards Da'wah Values in Bid'ah Films." The purpose of this research is to identify the da'wah values contained in the Bid'ah film and analyze the perception of students of the Da'wah Management Study Program of UIN Raden Fatah Palembang towards these values. This study uses a qualitative approach with the type of field research. Data collection techniques are carried out through observation, interviews, and documentation, which are then analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the Bid'ah film contains da'wah values that include aspects of faith, sharia, and morals. Students' perception of the film is divided into three dimensions, namely cognitive, affective, and conative. In the cognitive dimension, students are able to understand the message conveyed; In the affective dimension, there is a response in the form of acceptance and critical attitudes; Meanwhile, in the contive dimension, some students are encouraged to be more selective in understanding religious teachings. Thus, the film Bid'ah can function as an effective da'wah medium, even though it causes various perceptions among the audience. Therefore, critical understanding is needed so that the message conveyed can be received appropriately.